Astrocytes‐derived extracellular vesicles in motion at the neuron surface: Involvement of the prion protein. Issue 9 (12th July 2021) - D'Arrigo, Giulia; Gabrielli, Martina; Scaroni, Federica; Swuec, Paolo; Amin, Ladan; Pegoraro, Anna; Adinolfi, Elena; Di Virgilio, Francesco; Cojoc, Dan; Legname, Giuseppe; Verderio, Claudia
Abstract: Astrocytes‐derived extracellular vesicles (EVs) are key players in glia‐neuron communication. However, whether EVs interact with neurons at preferential sites and how EVs reach these sites on neurons remains elusive. Using optical manipulation to study single EV‐neuron dynamics, we here show that large EVs scan the neuron surface and use neuronal processes as highways to move extracellularly. Large EV motion on neurites is driven by the binding of EV to a surface receptor that slides on neuronal membrane, thanks to actin cytoskeleton rearrangements. The use of prion protein (PrP)‐coated synthetic beads and PrP knock out EVs/neurons points at vesicular PrP and its receptor(s) on neurons in the control of EV motion. Surprisingly, a fraction of large EVs contains actin filaments and has an independent capacity to move in an actin‐mediated way, through intermittent contacts with the plasma membrane. Our results unveil, for the first time, a dual mechanism exploited by astrocytic large EVs to passively/actively reach target sites on neurons moving on the neuron surface.